Damage control of epithelial barrier function in dynamic environments - Tomohito Higashi; Akira C. Saito; Hideki Chiba (European Journal of Cell Biology, 2024)
Epithelial tissues cover the surfaces and lumens of the internal organs of multicellular animals and crucially contribute to internal environment homeostasis by delineating distinct compartments within the body. This vital role is known as epithelial barrier function. Epithelial cells are arranged like cobblestones and intricately bind together to form an epithelial sheet that upholds this barrier function. Central to the restriction of solute and fluid diffusion through intercellular spaces are occluding junctions, tight junctions in vertebrates and septate junctions in invertebrates. As part of epithelial tissues, cells undergo constant renewal, with older cells being replaced by new ones. Simultaneously, the epithelial tissue undergoes relative rearrangement, elongating, and shifting directionally as a whole. The movement or shape changes within the epithelial sheet necessitate significant deformation and reconnection of occluding junctions. Recent advancements have shed light on the intricate mechanisms through which epithelial cells sustain their barrier function in dynamic environments. This review aims to introduce these noteworthy findings and discuss some of the questions that remain unanswered.